Impact of droplets on liquid films in the presence of surfactant - Che,Z; Matar,OK (Langmuir, 2017)
The impact of droplets on liquid films is ubiquitous in natural and industrial processes, and surfactants can significantly alter the impact process by changing the local surface tension. Here we study the impact of droplets on liquid films in the presence of surfactant using high-speed photography, and reveal the flow pattern by dye-tracing. The effects of the droplet size and speed, and the initial film thickness on the impact process are elucidated. The results show that the flow is significantly affected by adding surfactant to the droplet, the liquid film, or to both phases. In particular, the film dye patterns form concentric circles and flower-shaped structures at low and high droplet Weber numbers, respectively. We also show how surfactant-induced Marangoni stresses modify these flow patterns, and alter the characteristics of the phenomena associated with the impact process, such as the propagation of capillary waves, the evolution of the crown, and the formation of secondary droplets. During the impact of surfactant droplets on thin water films, the Marangoni stresses can be sufficiently strong so as to drive film dewetting.